The Seeds of Ideology: Historical Immigration and Political Preferences in the United States - Paola Giuliano; Marco Tabellini (Institute of Labor Economics (IZA), 2020)
We test the relationship between historical immigration to the United States and political ideology today. We hypothesize that European immigrants brought with them their preferences for the welfare state, and that this had a long-lasting effect on the political ideology of US born individuals. Our analysis proceeds in three steps. First, we document that the historical presence of European immigrants is associated with a more liberal political ideology and with stronger preferences for redistribution among US born individuals today. Next, we show that this correlation is not driven by the characteristics of the counties where immigrants settled or other specific, socioeconomic immigrants' traits. Finally, we conjecture and provide evidence that immigrants brought with them their preferences for the welfare state from their countries of origin. Consistent with the hypothesis that immigration left its footprint on American ideology via cultural transmission from immigrants to natives, we show that our results are stronger when inter-group contact between natives and immigrants, measured with either intermarriage or residential integration, was higher. Our findings also indicate that immigrants influenced American political ideology during one of the largest episodes of redistribution in US history — the New Deal — and that such effects persisted after the initial shock.
Keywords: D64; D72; H2; J15; N32; Z1; 330; immigration; culture; political ideology; preferences for redistribution